PENGEMBANGAN MULTIMEDIA VIDEO PEMBELAJARAN PENGOPERASIAN MESIN JAHIT INDUSTRI - Erni Rizki Hernawati; Cucu Ruhidawati (Fesyen Perspektif, 2016)
Based on the preliminary studies on the subjects studied this research review develoment of multimedia instructional videos industrial sewing machine operation. This study aims to identify learning materials, create a multimedia design instructional videos, perform and analysis of the results of validation. The proper method for this study is the method of approach R D (Research and Development). This study was conducted in Education Studies Program dressmaking Family Welfare Department of Education Faculty of Technical Education and Vocational Education University of Indonesia. The study population is learning materials expert and multimedia experts. Results of the validation by experts of material to get an average value of 94,2% percentage feasibility, by multimedia experts earn an average percentage of 80,6%. The tests concluded based on a standard feasibility of developing  multimedia instructional videos industrial sewing machine operation to fall into the category fit for use.